Cytokine profiling and transcriptomics in mononuclear cells define immune variants in Meniere Disease - Flook, Marisa; Rojano, Elena; Gallego-Martinez, Alvaro; Escalera-Balsera, Alba; Perez-Carpena, Patricia; Moleon, M. del Carmen; Gonzalez-Aguado, Rocio; Rivero de Jesus, Victoria; Domínguez-Durán, Emilio; Frejo, Lidia; G. Ranea, Juan A.; Lopez-Escamez, Jose Antonio (Genes and immunity, 2024)
Meniere Disease (MD) is a chronic inner ear disorder characterized by vertigo attacks, sensorineural hearing loss, tinnitus, and aural fullness. Extensive evidence supporting the inflammatory etiology of MD has been found, therefore, by using transcriptome analysis, we aim to describe the inflammatory variants of MD. We performed Bulk RNAseq on 45 patients with definite MD and 15 healthy controls. MD patients were classified according to their basal levels of IL-1β into 2 groups: high and low. Differentially expression analysis was performed using the ExpHunter Suite, and cell type proportion was evaluated using the estimation algorithms xCell, ABIS, and CIBERSORTx. MD patients showed 15 differentially expressed genes (DEG) compared to controls. The top DEGs include IGHG1 ( p = 1.64 × 10 −6 ) and IGLV3-21 ( p = 6.28 × 10 −3 ), supporting a role in the adaptative immune response. Cytokine profiling defines a subgroup of patients with high levels of IL-1β with up-regulation of IL6 ( p = 7.65 × 10 −8 ) and INHBA ( p = 3.39 × 10 −7 ) genes. Transcriptomic data from peripheral blood mononuclear cells support a proinflammatory subgroup of MD patients with high levels of IL6 and an increase in naïve B-cells, and memory CD8 + T cells.